Public Perceptions of Delays in the Release of Police Body-Worn Camera Footage - Bush, Christopher L (2020)
Delays in the release of police body-worn camera (BWC) video footage have amplified public concerns about police misconduct. People question law enforcement transparency when video from BWCs is not shared with the community in a timely manner. The qualitative case study explores the life experiences of the community and the victims’ family related to delays in the release of police BWC footage. Mettler and Sorelle’s policy feedback theory was used for the study’s theoretical framework. The research questions focus on understanding the lived experiences and perceptions of community relationships with law enforcement around transparency, communication, and information sharing. A qualitative study was used to examine 13 participants to determine which factors influence perceptions of law enforcement by the community and the victim’s family when there is delay in the release of BWC video. In addition, I focused on families who have been directly impacted and members of the community who have been indirectly impacted when police BWC video was delayed. Results show that both the community and the victim’s family members are requesting changes to community policing initiatives for better community engagement and for building positive relationships, trust, transparency, police legitimacy, and communication. This study presents law enforcement and society with insight on how to improve public perceptions